Accidents in thyroid surgery - Villarán del Risco, Carlos J. (1956)
Being short on time that circumstances impose on our presentation. I have to devote to reviewing some of the accidents to which it is exposed the surgeon involved in the thyroid; precisely those in which personal experience regret, is subject, that ungrateful, makes me covered awarded exceed 15 minutes and we have chosen, because of recent advances in diagnostic and pre- and postoperative therapy, also exploited surgical care of thyroid patients by reducing mortality averages negligent figures, and better cures to their highest levels; the "sense of security" that encourage, have led to greater radicality ablations; , and these in turn an upturn in the post-operative, I think morbidity must be upgraded.